PENERAPAN SENAM KAKI DIABETES MELITUS TERHADAP PERUBAHAN KADAR GULA DARAH PADA PASIEN DM TIPE II DIWILAYAH KERJA PUSKESMAS MACCINI SAWAH - Lisda Adinan; Sunarti Sunarti; Mardiah Mardiah (Jurnal Kesehatan, 2025)
Background: Diabetes melitus is a group of metabolic diseases characterized by hyperglicemia that occurs because the panckreas is unable to secrete insulin, has impaired insulin action, or both. Diabetes treatment involves two main strategis, namely pharamacological and non-pharamacological therapy. One of the  no-pharamacological treatments is physical exercise, where physical therapy such as diabetic foot exercise is given to maintain blood flow sensitivity in the feet of pattient.Objective:This study aims to determine the application of diabetic foot exercise on blood glucose level changes in type 2 diabetes melitus patients in the working area of maccini sawah health center. Method : This study used a case study design with a nursing care model for patients with type 2 diabetes melitus, which included assessment, nursing diagnisis, intervention, implementation, and evaluation. Results : Based on the nursing assessment, where obtained from patient Mrs.S, 53 year old, with a histiry of type 2 diabetes melitu, whose main complaint was numbness in the lower extremities. The GDS result was 203 mg/dl, so the nursing diagnosis that appeared in Mrs.S was unstable blood glucose levelsrelated to insulin resistance ( D.0027). A nursing intervention provided in the form of physical exercise, namely diabetic foot exercise,for 3 days. The results showed a change in blood glucose levels, with a GDS: value of 170 mg/dl. Conclusion: The application of diabetic foot exercise conducted by the researcher was able to reduce blood glucose levels in diabetes melitus patients. For diabetes melitus patients, performing diabetic foot exercises correctly and properly can help in controling blood glucose levels